The impact of credit types on household savings levels in South Africa - Naidoo, Jeremy (Graduate School of Business (GSB), 2019)
Despite robust economic growth in post-apartheid South Africa, we have consistently seen high unemployment and severe income inequality amongst its people. Arguably this has resulted in a culture of dependence on consumer credit; consumers are spending future income by using credit. This could result in a decrease in household savings levels amongst ordinary South Africans. Many studies have referred to an increase in consumer credit to supplement people’s income support or to offset low wages. This has a major impact on consumers who then find themselves over-indebted due to economic shocks and this could result in a negative impact on disposable income. The study investigates how the various types of credit play a major role on household savings levels in South Africa, and the analysis done in this study, on the various credit types, highlights the differences between secured type credit and unsecured type credit. The analysis of the relationship between the various credit types on household saving levels in South Africa was done using empirical data from 2008 up to 2106. The data used in the study was extracted from National Credit Regulator, as well as household savings data extracted from South African Reserve Bank. The methodology involves the use of the bounds test approach to co-integration using Autoregressive Distribution Lag models and Granger Causality testing to establish causality. The results indicated that overall there was a positive relationship between total credit and household savings levels in South Africa. However, we also find a significant negative relationship between unsecured credit and household savings levels in South Africa. Further analysis also found that three out of the four credit types tested resulted in a decrease in household savings levels. Given the importance of savings levels to the economy, and also the high risk of economic shocks in South Africa, this study concludes with proposals for tighter regulation in the consumer credit market. It further argues for robust mechanisms to be put in place by stake holders to ensure that consumers are cushioned against economic shocks that could result in over-indebtedness.